Local energy businesses in the United Kingdom: Clusters and localism determinants based on financial ratios. (15th January 2022) - Fuentes González, Fabián; Webb, Janette; Sharmina, Maria; Hannon, Matthew; Braunholtz-Speight, Timothy; Pappas, Dimitrios
Abstract: This paper presents the first financial analysis of the United Kingdom's local energy business sector. This analysis relies on financial ratios and degrees of localism as inputs for descriptive statistics, cluster, and canonical discriminant analyses. Our findings suggest that privately-owned energy businesses, typically with limited commitments to localities, account for the great majority of sectoral assets and turnover, and are in comparatively good financial condition. Highly-local energy businesses typically have low profitability and high reliance on debt. The latter is the key variable differentiating them from other less local energy businesses. Moreover, we find financial commonalities within different groups of local energy businesses, which correlate with their specific level of localism. In the context of increasing digitalisation in energy markets, more technological innovation may help strengthen local energy businesses' revenue sources and value creation. Further research is needed in terms of investability, specific financing terms and conditions, and geographical aspects of value creation, retention, and delivery to localities. This work can improve the understanding of sectoral dynamics and development needs, with value for policy making to incentivise investment in this emerging sector. Highlights: An analysis of the United Kingdom's local energy business sector is presented. The analysis relies on financial ratios and estimates for degrees of localism. Highly-local businesses typically have low profitability and high reliance on debt. Businesses with limited local commitment usually have a good financial condition. Research on investability, financing, and locational value creation are needed.